Analisis Pengaruh Arus Kas Operasi(AKO), Arus Kas Investasi(AKI), dan Arus Kas Pendanaan(AKP) terhadap Harga Saham pada PT. Sidomuncul Tbk - Feri Irawan; Aris Munandar; Ovriyadin Ovriyadin (CV. Denasya Smart Publisher, 2026)
The purpose of this study is to examine the effect of Operating Cash Flow (OCF), Investing Cash Flow (ICF), and Financing Cash Flow (FCF) on the stock price of PT Sido Muncul Tbk. The statement of cash flows is one of the most important sources of information used by investors to assess a company's financial performance and to support investment decision-making. Since the cash flow statement reflects the company's financial condition, changes in its components are expected to influence stock price movements.This study employs a quantitative research approach using secondary data, consisting of the annual financial statements and stock price data of PT Sido Muncul Tbk. Multiple linear regression analysis was applied to examine the relationship between the independent and dependent variables. The sample was selected using a purposive sampling technique, resulting in financial statement data that met the research criteria over a 13-year observation period. The analysis included classical assumption tests, namely normality, heteroscedasticity, multicollinearity, and autocorrelation tests. Hypothesis testing was conducted using the partial test (t-test), simultaneous test (F-test), and the coefficient of determination (R²).The results indicate that operating cash flow has a negative effect on stock prices, investing cash flow has a positive effect on stock prices, and financing cash flow has a negative effect on stock prices. Simultaneously, operating cash flow, investing cash flow, and financing cash flow have a positive effect on stock prices.